2011
DOI: 10.1111/j.1365-2559.2011.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is highly expressed in severely dystrophic muscle and seems to play a role in muscle regeneration and fibrosis

Abstract: Several fibrosis-related factors are greatly altered in severely dystrophic skeletal muscle. Osteopontin was the most conspicuously upregulated, both as transcript and as protein, in muscle fibres and infiltrating cells, indicating an intimate involvement in fibrosis, and also in inflammation and muscle regeneration, although its precise roles in these processes remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 50 publications
7
42
0
2
Order By: Relevance
“…Associations of miRNA (miR-21, miR-29a, miR-29c) expression levels with levels of collagen I and VI transcripts and proteins (considered markers of fibrosis, [61]), and patient age (considered an indicator of disease progression [18]), were assessed by Pearson's linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations of miRNA (miR-21, miR-29a, miR-29c) expression levels with levels of collagen I and VI transcripts and proteins (considered markers of fibrosis, [61]), and patient age (considered an indicator of disease progression [18]), were assessed by Pearson's linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We found that miR-21 was upregulated in DMD muscle, and that levels correlated directly with COL1A1 and COL6A1 transcript levels (markers of fibrosis, [61]) and also age (marker of disease progression [18]). …”
Section: Mir-21 Upregulation and Its Implicationsmentioning
confidence: 96%
“…Osteopontin has been described as a component of the inflammatory milieu of dystrophin-deficient muscles (Haslett et al 2002;Porter et al 2002;Uaesoontrachoon et al 2008;Zanotti et al 2011), and muscles of individuals with dystrophies caused by deficiencies of other proteins (Turk et al 2006). As osteopontin promotes inflammation and fibrosis in a wide range of tissues (Mori et al 2008;Pardo et al 2005), Spencer and colleagues tested the hypothesis that osteopontin may influence inflammation and fibrosis in dystrophin deficient muscles by crossing dystrophin-deficient mdx mice with osteopontin-null mice to produce double mutant mice (DMM), lacking both dystrophin and osteopontin (Vetrone et al 2009).…”
Section: Osteopontin and Disease Severity In Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Expression of OPN was demonstrated in chondrocytes [19], fibroblasts [20], dendritic cells, macrophages and T-cells [21], hepatocytes [22], smooth muscle cells [23], skeletal muscle [24], endothelial cells [25], inner ear [26], brain [27], placenta and mammary glands [28] or kidney [29], and the protein may be assayed in some biological fluids, including blood, urine, milk and semen [1,18].…”
Section: Objectivementioning
confidence: 99%